Analysis of the capital structure: an empirical study of listed companies in UK - Huo, Erman (2011)
The two competing models of financial investment decisions, the trade-off and pecking order models, share many predictions of financial leverage. The former indicates that firms gradually adjust the debt-equity ratio towards an optimum. The latter predicts that external financing is driven by financial deficit of internal funding. The basic pecking order model seems to have more time-series explanatory power than static trade-off model. These two models are contradicting on hypothesis of leverage variation driven by some variables. This paper tests the traditional trade-off model against the pecking order model of corporate financing in UK listed firms. It is shown that this test provides mixed evidence for the dominance of these two models.